A study of nonglaucomatous optic neuropathies in a teaching hospital in Western Maharashtra - Manasa Reddy Kakulavaram; Ajit Kamalakar Joshi (Journal of Clinical Ophthalmology and Research)
Background: Nonglaucomatous optic neuropathy (NGON) is defined as clinical evidence of optic nerve impairment without glaucomatous field/disc changes. Etiology is diverse and elusive in many patients. Causes of NGON include traumatic, compressive, inflammatory, demyelinating, toxic, nutritional, hereditary, vascular, infiltrative, and idiopathic. NGON disorders can be misdiagnosed as glaucoma and can be preventable or life-threatening. In some, fellow eye involvement is common. This can lead to inadequate management and influence prognosis which can be prevented by multispecialty approach. Physicians and ophthalmologists must be vigilant against threatening NGON forms. It is essential to track burden as most literature focused on particular NGON subtype. AIM: The aim was to study the clinical presentation of NGON in a teaching hospital. Setting and Design: This was a prospective, hospital-based, cross-sectional, observational study. MATERIALS AND METHODS: A total of 86 eyes of 61 NGON patients were studied from January 2021 to June 2022 in a tertiary care hospital. Detailed history and comprehensive ophthalmic examination were performed in ambulatory patients. Nonambulatory patients were examined using torchlight. Ancillary investigations were performed, to confirm the clinical diagnosis wherever applicable. Statistical Analysis: Microsoft Excel was used for statistical analysis. Results: The mean age of study patients was 44.87 ± 16.05 years with a male: female ratio of 2.8:1. Unilateral eye involvement was seen in 36 (59.02%). Best-corrected visual acuity = 3/60–1/60 was noted in 41 (47.67%) patients. Red-green defect and contrast sensitivity were reduced by 59.30% and 66.28%, respectively. Relative afferent pupillary defect (RAPD) was noted in 52.46% of patients with Grade 5 RAPD in 40.63%. The most common visually evoked potential type and visual field defect noted were axonal and central scotoma (n = 31 [36.05%] and n = 26 [30.23%]), respectively. Traumatic optic neuropathy was diagnosed in 15 (24.59%) followed by inflammatory optic neuritis in 11 (18.04%) patients. Conclusion: Diagnosing cause of NGON in clinical practice is challenging, but emerging burden cannot be neglected. Knowledge of various NGON types helps narrow differential diagnoses and execute efficient, targeted workup. Timely recognition alters visual, neurological prognosis and saves the lives of patients sometimes.